1988
DOI: 10.1111/j.1476-5381.1988.tb11709.x
|View full text |Cite
|
Sign up to set email alerts
|

Control of interval‐force relation in canine ventricular myocardium studied with ryanodine

Abstract: 1 The mechanism of post-extrasystolic, rest and frequency potentiation was studied in canine isolated ventricular muscle. 2 Ryanodine, which impairs Ca availability from the sarcoplasmic reticulum (SR), reduced the amplitude of the extrasystole less than that of the steady state contraction. Ryanodine also inhibited post-extrasystolic potentiation and converted rest-potentiation into rest depression. Restpotentiation was blocked preferentially by ryanodine compared to post-extrasystolic potentiation. An increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 29 publications
3
11
0
Order By: Relevance
“…TFP at 300 M inhibits both steady-state and PRP30 contractions. Because the ability of a rest interval to augment contractility depends more on SR Ca 2ϩ than on Ca 2ϩ from other sites (Bers, 1985;Sutko et al, 1986;Bose et al, 1988;, these results also suggest the TFP-dependent inhibition observed in these experiments involves changes to the regulation of SR Ca 2ϩ . Analogous experiments, performed in our laboratory and designed to evaluate the effects of daunorubicin on cardiac contractility, yielded results similar to those observed with TFP .…”
Section: Resultssupporting
confidence: 61%
“…TFP at 300 M inhibits both steady-state and PRP30 contractions. Because the ability of a rest interval to augment contractility depends more on SR Ca 2ϩ than on Ca 2ϩ from other sites (Bers, 1985;Sutko et al, 1986;Bose et al, 1988;, these results also suggest the TFP-dependent inhibition observed in these experiments involves changes to the regulation of SR Ca 2ϩ . Analogous experiments, performed in our laboratory and designed to evaluate the effects of daunorubicin on cardiac contractility, yielded results similar to those observed with TFP .…”
Section: Resultssupporting
confidence: 61%
“…After complete mechanical stabilization of the muscle at a basal stimulation frequency of 1 Hz, the experimental protocol was started. For post-rest contractions, electrical stimulation of the muscle strips was switched off at steady state conditions for increasing intervals (2,5,10,20,30,40,50,60, 120, and 240 s). Upon restimulation, the first beat was evaluated for post-rest changes in isometric twitch tension (mN/mm 2 ), maximum rate of tension rise ( ϩ dT/dt max ), maximum rate of tension decline ( Ϫ dT/dt max ) time to peak tension (TPT) and time to 50% and 95% relaxation.…”
Section: Methodsmentioning
confidence: 99%
“…However, many patients in whom the extent of PESP might potentially be of importance are studied during treatment with a range of inotropically active drugs. It has been demonstrated, on the basis of in vitro studies, that calcium availability at the level of the myofibrils is a critical determinant of PESP [2,[10][11][12]. Consistent with this, it appears that calcium antagonist drugs and ryanodine inhibit PESP [2,10,13].…”
Section: Introductionmentioning
confidence: 78%
“…This phenomenon has been extensively investigated both in vitro [2][3][4] and in vivo [5,6]. The maximum rate of rise of left ventricular pressure (LV+dP/dtmax) of a postextrasystole is a function of both the extrasystolic test pulse interval (ETPI), and the interval preceding the postextrasystole.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation